Pixelated metasurfaces for terahertz absorption and polarization conversion - Rai S.; Bhattacharyya S.; Lakhtakia A. (My University, 2025)
As electromagnetic research in the terahertz regime is expanding to encompass spectroscopy for medical diagnostics, imaging, security, defense, etc., terahertz metasurfaces are being designed and implemented for absorbers, antennas, cloaks, polarizers, and other devices. © 2019 URSI. All rights reserved.